2019
DOI: 10.1159/000500558
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding Parosmia: An fMRI Study

Abstract: <b><i>Introduction:</i></b> A number of patients with a diminished sense of smell also can suffer from parosmia. These patients with such a qualitative smell disorder are often more severely affected than patients exhibiting only a quantitative smell disorder. Qualitative smell disorders have heretofore been poorly investigated. The focus of the present study was, using functional MRI, to compare the central processing of olfactory stimulation in patients with qualitative smell disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 27 publications
2
47
0
1
Order By: Relevance
“…The present observation of pleasantness evoked by OFC stimulation does not dispute the suggestion of Nigri et al [20] that the medial OFC is involved in integrative olfactory processing even if they tested only unpleasant odorants. A very recent fMRI paper comparing patients with olfactory impairment with versus without parosmia, a condition where unpleasant odorous percepts are elicited by normal odors, showed that parosmia patients had higher activations in the putamen and thalamus but not in the OFC [33]. This goes in line with the present data that the OFC is probably not the main generator of unpleasant olfactory symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The present observation of pleasantness evoked by OFC stimulation does not dispute the suggestion of Nigri et al [20] that the medial OFC is involved in integrative olfactory processing even if they tested only unpleasant odorants. A very recent fMRI paper comparing patients with olfactory impairment with versus without parosmia, a condition where unpleasant odorous percepts are elicited by normal odors, showed that parosmia patients had higher activations in the putamen and thalamus but not in the OFC [33]. This goes in line with the present data that the OFC is probably not the main generator of unpleasant olfactory symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…A decrease in olfactory bulb volume 23, 24 and a significant loss of grey matter volume 25 has been demonstrated in parosmic participants. Further evidence of central mechanisms has been published recently showing different fMRI activation patterns in parosmic participants compared to hyposmics 26 . Increased activation in the thalamus and the putamen was observed in the parosmic participants, the latter being of relevance since it is connected to the olfactory cortical networks and has been associated with the perception of disgust.…”
Section: Discussionmentioning
confidence: 94%
“…Because many of these areas are critically involved in olfactory quality discrimination and odor memory, it has been speculated that the parosmia was associated with structural changes in a neuronal network crucial for odor discrimination and memory. A functional MRI study demonstrated that hyposmic patients with parosmia exhibited a strong activation in the thalamus, known to be related to directed attention in relation to the sense of smell, and the putamen that is implicated in the recognition of disgust signals (48).…”
Section: Discussionmentioning
confidence: 99%